Unveiling The Myth of High Recurrence Rate of Extracranial Arteriovenous Malformations of The Head and Neck: Systematic Review of Case Reports and Case Series [version 2; peer review: 2 approved] - Sagung Rai Indrasari; Danu Yudistira; Camelia Herdini; Agustian Winarno Putra (F1000Research)
Background Arteriovenous malformations (AVMs) in the head and neck pose a challenge in their management due to their local aggressiveness and high recurrence risk. This study aimed to analyze literature on head and neck AVM recurrence post-treatment and identify the most effective strategy with a lower recurrence rate. Objectives To analyse existing literature on the recurrence of head and neck AVMs following treatment. Our goal was to identify the most effective treatment option with a lower recurrence rate. Methods We conducted a thorough literature search using PubMed, ScienceDirect, and Scopus, from year 2000 to the present. Our analysis focused on key endpoints, specifically the recurrence rates of head and neck AVMs following various treatment approaches. Results Out of the initial pool of 108 screened articles, a total of 83 patients were deemed suitable for inclusion in the literature review. The reviewed articles demonstrated that appropriate diagnostic tests were documented in 95% of the included studies. Among the patients, 37.3% had previously undergone interventions and were currently dealing with regrowth masses. Notably, 55.4% of patients underwent a combined approach involving both endovascular and surgical methods, while 25.3% opted for a surgical-only approach, and only 19.3% pursued an endovascular-only approach. The studies showed a promising curing rate of AVMs, with a success rate of 94%, albeit with a complication rate of 32.5%. The average follow-up duration for all patients was 26 months, with a standard deviation of 20.5 months. Out of the 83 patients, 5 experienced recurrence, with single-modality approach. Interestingly, no patients who received a multi-modality of treatments experienced recurrence or regrowth of the AVM mass within the follow up period. Conclusion The multi-modality approach outperformed single-modality treatments in preventing AVM recurrence. These findings highlight the importance of a comprehensive and multidisciplinary approach in the management of these complex vascular anomalies. PROSPERO: CRD42023490871 registered on 17/12/2023